The persistence of neoliberal logics in faculty evaluations amidst Covid‐19: Recalibrating toward equity. Issue 2 (10th February 2022) - Mickey, Ethel L.; Misra, Joya; Clark, Dessie
Abstract: In this paper, we theorize the intersectional gendered impacts of COVID‐19 on faculty labor, with a particular focus on how institutions of higher education in the United States evaluate faculty labor amidst the COVID‐19 transition and beyond. The pandemic has disrupted faculty research, teaching, and service in differential ways, having larger impacts on women faculty, faculty of color, and caregiving faculty in ways that further reflect the intersections of these groups. Universities have had to reconsider how evaluation occurs, given the impact of these disruptions on faculty careers. Through a case study of university pandemic responses in the United States, we summarize key components of how colleges and universities shifted evaluations of faculty labor in response to COVID‐19, including suspending teaching evaluations, implementing tenure delays, and allowing for impact statements in faculty reviews. While most institutional responses recenter neoliberal principles of the ideal academic worker that is both gendered and racialized, a few universities have taken more innovative approaches to better attend to equity concerns. We conclude by suggesting a recalibration of the faculty evaluation system – one that maintains systematic faculty reviews and allows for academic freedom, but requires universities to take a more contextualized approach to evaluation in ways that center equity and inclusion for women faculty and faculty of color for the long term.